2017
DOI: 10.1016/j.ijpsycho.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on functional connectivity associated with feedback processing and prediction error: Phase coupling of theta-band oscillations in twins

Abstract: Detection and evaluation of the mismatch between the intended and actually obtained result of an action (reward prediction error) is an integral component of adaptive self-regulation of behavior. Extensive human and animal research has shown that evaluation of action outcome is supported by a distributed network of brain regions in which the anterior cingulate cortex (ACC) plays a central role, and the integration of distant brain regions into a unified feedback-processing network is enabled by long-range phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…ACE models were chosen based on previous work demonstrating that for many similar task-related frontal EEG components (Anokhin et al, 2008; Demiral et al, 2017; Malone et al, 2017), ACE models fit better than other potential twin models, such as ADE non-additive genetic dominance (D) effect models. The magnitude of the influence of each ACE latent variable on a phenotype is estimated by comparing the expected covariance matrix, derived from the known correlations between family members with respect to A (expected twin correlation: MZ = 1, DZ = 0.5), C (MZ and DZ = 1), and E (MZ and DZ = 0), to the observed covariance matrix.…”
Section: Methodsmentioning
confidence: 99%
“…ACE models were chosen based on previous work demonstrating that for many similar task-related frontal EEG components (Anokhin et al, 2008; Demiral et al, 2017; Malone et al, 2017), ACE models fit better than other potential twin models, such as ADE non-additive genetic dominance (D) effect models. The magnitude of the influence of each ACE latent variable on a phenotype is estimated by comparing the expected covariance matrix, derived from the known correlations between family members with respect to A (expected twin correlation: MZ = 1, DZ = 0.5), C (MZ and DZ = 1), and E (MZ and DZ = 0), to the observed covariance matrix.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding reward-related processing, such as monetary tasks, no studies using EEG or MEG measures were found in FC in alcohol dependence. However, a study carried out in healthy population indicates changes in FC ( 133 ), reflected by increases in theta synchronization between frontal region and mostly parietal areas during the loss condition and greater theta FC within posterior regions during the gain condition. Moreover, this study is carried out in co-twins and they find a genetic heritability of fronto-parietal connectivity in theta during the loss condition, indicating that reward evaluation of negative outcomes could be genetically transmitted.…”
Section: Evidence In Other Neuropsychophysiological Measuresmentioning
confidence: 99%
“…Despite the quite diverse outcomes, there seems to be an agreement upon their role in the brain, and some of them have even been proposed as possible markers of alcohol effects in the brain or as vulnerability markers, such as changes in theta connectivity ( 131 ). In this manner, alterations in FC of theta might indicate changes in the inhibitory neuronal system, related to GABAergic and cholinergic neurotransmission ( 112 ), as well as emotional and motivational processing ( 133 ), whereas beta and alpha FC might reflect supervision and coordination processes involved in brain activation and deactivation systems ( 134 ).…”
Section: Evidence In Other Neuropsychophysiological Measuresmentioning
confidence: 99%
“…We previously showed heritability of brain EEG signals in error monitoring for twins with Mx model [45].…”
Section: Intra-pair Twin Correlations and Genetic Heritability Analysismentioning
confidence: 99%